Design and development of modular magnetic bio-inspired autonomous underwater robot – MMBAUV. (1st April 2023) - Wright, Marvin; Xiao, Qing; Dai, Saishuai; Post, Mark; Yue, Hong; Sarkar, Bodhi
Abstract: This paper describes the design and construction of a magnetically coupled modular bio-inspired underwater robot named the Modular Magnetic Bio-Inspired Underwater Vehicle (MMBAUV). Designed to form a traveling wave to mimic efficient Body Caudal Fin (BCF) swimming and manoeuvring, its modularity allows for flexible system setup and offers an opportunity for redundancy and cost reduction through a common design structure. The specific feature of this design presents a novel application of a permanent synchronous magnetic coupling between neighbouring modules with a rotational degree of freedom (DoF). The actuated magnetic coupling provides a reliable and low maintenance solution to the fundamental issues of water tightness of flexible underwater structures. When encountering extreme conditions, the magnetic coupling allows the safe decoupling of the modules increasing the survivability of the robotic system. Presented lab testing results demonstrate the function of the design and provide initial evidence of its thrust generation and manoeuvrability. Highlights: Design of Modular Magnetic Bio-inspired Robot that mimics Body Caudal Fin (BCF) Fish swimming by forming a traveling wave along its centre line. Description of design and development of prototype with detailed description of magnetic coupling. Experimental lab testing to assess performance for different caudal fin materials and combination of swimming kinematic parameters.